THE ROLE OF ARTIFICIAL INTELLIGENCE IN IMPROVING DIGITAL LITERACY OF INTERNATIONAL STUDENTS THROUGH THE UNPAM INDONESIA – UMT MALAYSIA COLLABORATIVE PROGRAM - Wijoyo, Agung; Santoso, Bambang; Rokhmanila, Siti (Universitas Pamulang, 2025)
The international Community Service Program (PKM) between Pamulang University (UNPAM) and Universiti Malaysia Terengganu (UMT) aims to improve students' digital literacy and artificial intelligence (AI) skills through intensive training and collaborative projects. The program addressed students' low understanding of AI concepts and limited access to technology-based training and projects. The program included interactive workshops and hands-on AI model development using Python and TensorFlow. Thirty students from UMT participated in the two-week hybrid program. Methods included observation, pre- and post-test questionnaires, and collaborative project evaluation. Results showed a significant increase in participants' AI understanding scores, from an average of 58.3 to 82.7. Furthermore, participants completed AI mini-projects and demonstrated improved programming skills and understanding of technology ethics. The program also facilitated international collaboration, strengthened academic networks, and encouraged the development of AI-based digital entrepreneurship. This UNPAM–UMT collaboration serves as a replicable model of technology-based community service to support the transformation of higher education in Southeast Asia.